(untitled) (مجلة ديالى للبحوث الانسانية, 2021)
The recent developments that Arab states have witnessed, especially after Arab Spring, have raised many questions including whether or not these developments have led to a shift in the attitude of the Western-world countries towards Arab societies, including the Arab woman. This question creates an obvious need to find out how the British media portray Arab woman. The study is based on the hypothesis that the Arab woman is positively depicted in the British media. To achieve the aim of the study and verify its hypothesis, two types of procedures have been followed: theoretical and practical. The theoretical part consists of presenting a brief theoretical framework of Critical Discourse Analysis (CDA) including its main premises and approaches. However, the practical part consists of analyzing two articles written by British authors in the light of an eclectic model based mainly on Wodak (2001) and van Dijk’s (2000) models with some modifications to make the model more suitable for the purpose of the study. The results of the analysis have shown that the Arab woman is positively depicted in the British media which verifies the hypothesis adopted in the study.